Can Virtual Influencers Be Trusted Like Humans? A Social-Psychological Study in Indonesia - Agung Stefanus Kembau; Christian Haposan Pangaribuan; Devi Yurisca Bernanda; Fidelia Novena Doa (Jurnal Ilmu Perilaku, 2025)
. In Indonesia’s collectivistic yet mobile first marketplace, virtual influencers have evolved from eye catching avatars into algorithmic peers whose persuasive power rests on a blend of social conformity and personal enjoyment. Leveraging the Artificial Intelligence Device Use Acceptance (AIDUA) model, this study isolates primary (cognitive) and secondary (affective) appraisals to explain why users embrace—or recoil from—synthetic personae. A cross sectional online survey of 286 Indonesian social media users (aged 18 35) tested a structural model linking social influence and hedonic motivation to performance expectancy, anthropomorphism to effort expectancy, and both cognitions to discrete positive and negative emotions. Variance based SEM (SmartPLS 4) produced robust psychometrics and significant pathways: social influence (β = .34) and hedonic motivation (β = .46) jointly explained 45 % of performance expectancy, while anthropomorphism sharply reduced perceived effort (β = .61; R² = .38). Performance expectancy amplified positive emotion (β = .48) and effort expectancy mitigated negative emotion (β = −.41), with the model accounting for 42 % of positive and 29 % of negative affect. These results uncover “utilitarian collectivism”—a dual cognitive–affective engine wherein peer validation and hedonic thrill sustain utilitarian value—and position anthropomorphism as a usability heuristic rather than a mere novelty cue.